Fuels and new propellants : proceedings of the conference held in Milan by Federazione associazioni scientifiche e techniche, and sponsored by Consiglio nazionale delle ricerche - Casci, Corrado (International series on aeronautical sciences and space flight. Symposia, 1964)
Fuels and New Propellants.